Colocalization of cellular nanostructure using confocal fluorescence and partial wave spectroscopy - Chandler, John E.; Stypula‐Cyrus, Yolanda; Almassalha, Luay; Bauer, Greta; Bowen, Leah; Subramanian, Hariharan; Szleifer, Igal; Backman, Vadim (Journal of biophotonics, 2017)
A new multimodal confocal microscope has been developed, which includes a parallel Partial Wave Spectroscopic (PWS) microscopy path. This combination of modalities allows molecular‐specific sensing of nanoscale intracellular structure using fluorescent labels. Combining molecular specificity and sensitivity to nanoscale structure allows localization of nanostructural intracellular changes, which is critical for understanding the mechanisms of diseases such as cancer. To demonstrate the capabilities of this multimodal instrument, we imaged HeLa cells treated with valinomycin, a potassium ionophore that uncouples oxidative phosphorylation. Colocalization of fluorescence images of the nuclei (Hoechst 33342) and mitochondria (anti‐mitochondria conjugated to Alexa Fluor 488) with PWS measurements allowed us to detect a significant decrease in nuclear nanoscale heterogeneity (Σ), while no significant change in Σ was observed at mitochondrial sites. In addition, application of the new multimodal imaging approach was demonstrated on human buccal samples prepared using a cancer screening protocol. These images demonstrate that nanoscale intracellular structure can be studied in healthy and diseased cells at molecular‐specific sites. Instrumentation has been developed enabling colocalization of confocal fluorescence and nanoscale‐sensitive spectroscopic microscopy modalities. This combination allows sensing of the heterogeneity of nanoscale intracellular structure within specific fluorescently labeled organelles or molecular structures. To demonstrate the capabilities of this multimodal instrument, the effects on the heterogeneity of nanoscale structure were examined in the nuclei and mitochondria of HeLa cells treated with valinomycin, a potassium ionophore that uncouples oxidative phosphorylation.